Rola nowoczesnych technologii w kształtowaniu doświadczenia usługowego - Boguszewicz-Kreft, Monika (The Role of Modern Technologies in Creating Service Experience, 2009)
Utilization of modern technology enables service enterprises to offer diverse and customized products in the cost effective manner. Skillful utilization of human and technological potential combined together, enables enhancing client experience as well as distinguishing the service in the market, it also involves considerable financial benefits for businessmen. The development of new technologies provides more opportunities for engaging the client in service production process. That enters a new stream of perceiving client as an active individual, co-creating values and giving meaning to products in point of consumption.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 63-70